Pendidikan Agama dalam Keluarga terhadap Anak Usia Dasar: Kontekstualisasi Pemikiran Nurcholish Madjid - Baiti, Masnun; Bujuri, Dian Andesta; Hamzah, Amir; Yusnita, Erni (Fakultas Agama Islam Universitas Billfath, 2022)
This article describes an analysis result to Nurcholish Madjid’s thinking about the importance of religion education in the family toward age basic child. This research is liberary research. Data is obtained from the various literature as book and journal. Data is analyzed by content analysis technique which analyzes various sources and conclusions concerning religion education in the family toward age basic child perspective of Nurcholish Madjid. According to Nurcholish Madjid, religion education in the family to basic age child includes two dimensions which the first is divinity dimension including to faith, Islam, virtue, piety, sincere and resignation, gratitude, and patient. The second is and humanity dimension including to friendship, fraternity (ukhuwah), equality (al-musawwah), fair, positive thinking (husn-u’zh-zhann), humble (tawaddu), commitment (al-wafa), cordiality (insyirah), mandate (al-amanah, “amanah”), brave (iffah atau ta’affut), thrifty (qawamiyah), dan generous (al-munfiqun, doing infaq). A right action of parent which teach those good values by model and practice continually as pray, fast, alms, discipline of time, and independent, will be internalized into child’s self and make the child aware to actualize those values on the daily life since basic age.